93Nb NMR Study of (K, Na)NbO3-Doped SiO2–Na2O–Al2O3 Glasses - Otsuka, Takahito; Cicconi, Maria Rita; Dobesh, David; Schroeder, Barbara; Hayakawa, Tomokatsu (physica status solidi (b), 2022)
Aluminosilicate glasses containing octahedral NbO6 units are developed for future applications as optical materials. Soda-aluminosilicate glasses doped with Nb-based alkaline perovskite crystals (K0.5Na0.5NbO3 [KNN]) at different doping levels (2–30 mol%) are studied by 93Nb nuclear magnetic resonance (NMR) spectroscopy. The Al2O3 concentration in the starting soda-aluminosilicate glass matrix is varied from 5 to 17 mol% to investigate the influence of the composition of local Nb structures with 4–5, 6, and 7–8 fold-oxygen coordination on the optical properties of the glasses. The chemical shifts are analyzed by comparison with the 93Nb NMR data of reference crystals, including KNN, to determine the feasibility of producing more NbO6 octahedra in the aluminosilicate glasses, where these octahedra are expected to promote the development of optically active Nb-glass-ceramics. The data show that both glass polymerization and KNN content influence the Nb local environment. Therefore, an appropriate amount of Al2O3 combined with an adequate doping level of the KNN perovskite is required to achieve the desired optical features. Contrary to expectations, a higher KNN doping level is achieved with the starting depolymerized soda-aluminosilicate glass containing 5 mol% Al2O3, leading to perovskite-like structures of NbO6 octahedra in the resultant glass system.
CRIS-Team Scopus Importer:2022-06-03
Keywords: aluminosilicate glasses; glass-ceramics; local structure analysis; Nb NMR; NbO; nuclear magnetic resonance; perovskites

Alkali-Niobate aluminosilicate glasses: Structure and properties - Cicconi, Maria Rita; Dobesh, David; Schroeder, Barbara; Otsuka, Takahito; Hayakawa, Tomokatsu; de Ligny, Dominique (Optical Materials: X, 2023)
K0.5Na0.5NbO3 (KNN) based ceramics are considered optimal candidates to replace the toxic Pb-based piezoelectric materials; nonetheless, they are quite difficult to process. Therefore, obtaining an efficient glass-ceramic (GC) will have several advantages in lead-free piezoelectric production. The first step to developing advantageous functional GCs is to determine an adequate glass matrix and the network connectivity of the different structural entities depending on the bulk chemistry. Here, we investigated the structural variations occurring in aluminosilicate systems having Na2O/Al2O3 molar ratios from 1 to 5.7 upon the addition of KNN (0.4 up to 30 mol%) to understand how the bulk composition influences KNN incorporation and the properties of the glasses. Our study shows that more depolymerized aluminosilicate systems incorporate a larger amount of KNN because the Nb structural environment's evolution strongly depends on glass polymerization and the availability of charge compensator ions. No strong crosslinking between [SiO4], [AlO4], and [NbO6] structural entities was found, and there is an evolution from a heterogeneous environment with isolated [NbO6] units having different degrees of distortion to Nb–O–Nb linkages, up to the formation of clusters composed of corner-shared slightly distorted [NbO6]. All glass series tend to move toward these 3D clusters whenever the starting structure includes different entities or a more homogeneous environment. The evolution of the different niobate entities marks the changes in the properties that show non-linear variations with KNN content. Furthermore, the glass chemistry influences the crystallization kinetics, with activation energies for crystallization that vary from ∼300 ± 10 kJ/mol to ∼220 ± 10 kJ/mol depending on the alkali/Al2O3 molar ratios. The developed niobo-aluminosilicate glasses show high refractive indices, high transparency in the visible– NIR region and intense UV absorption. Therefore, these glasses are excellent candidates for photonic applications and optoelectronic devices. The stabilization of a perovskite-like phase upon crystallization confirms the potentiality for use as electro-optical glass-ceramics.
CRIS-Team Scopus Importer:2023-03-03
Keywords: Glass structure; Glass-ceramics; Optical properties; Raman spectroscopy

Influence of stress on the electromechanical properties and the phase transitions of lead-free (1-x)Ba(Zr0.2Ti0.8)O-3-x(Ba0.7Ca0.3)TiO3 - Gadelmawla, Ahmed; Dobesh, David; Eckstein, Udo; Grübl, Oliver; Ehmke, Matthias; Cicconi, Maria Rita; Khansur, Neamul Hayet; de Ligny, Dominique; Webber, Kyle Grant (Journal of Materials Science, 2022)
The influence of stress on the phase boundaries of polycrystalline lead-free perovskite (1 - x)Ba(Zr0.2Ti0.8)O-3-x(Ba0.7Ca0.3)TiO3 (x = 0.4, 0.5, and 0.6) was characterized through the temperature- and stress-dependent small-signal dielectric and piezoelectric response from - 150 to 200 degrees C under uniaxial compressive stress up to - 75 MPa. For all three compositions, the phase transition temperatures separating the rhombohedral, orthorhombic, tetragonal, and cubic phases were shifted to higher temperatures with an increase in the uniaxial mechanical loading, corresponding to a significant decrease in the dielectric and piezoelectric responses. Additional stress-dependent relative permittivity measurements up to - 260 MPa were conducted at four different constant temperatures (- 10, 10, 25, and 40 degrees C), revealing significant increases in the dielectric response, making these materials interesting for tunable dielectric applications. Furthermore, the stress-induced shift in phase transition temperatures was confirmed by in situ combined temperature- and stress-dependent Raman spectroscopy measurements under different constant uniaxial loads within the temperature range from 30 to 130 degrees C.
CRIS-Team WoS Importer:2022-09-16

The role of Ca/Zr ratio on the local structure and phase transitions in lead-free (Ba,Ca)(Zr,Ti)O3 - Dobesh, David; Gadelmawla, Ahmed; Miyazaki, Hidetoshi; Hinterstein, Manuel; Kimura, Koji; Maier, Juliana; Banerjee, Semanti; Zeair, Omar; Mehta, Sharly; da Silva, Lucas Lemos; Khansur, Neamul Hayet; Hayashi, Koichi; et al. (Journal of the European Ceramic Society, 2024)
In this study, the structural phase transitions are investigated as a function of composition and temperature for polycrystalline x(Ba0.7Ca0.3)TiO3-(1 − x)Ba(Zr0.2Ti0.8)O3 (x = 0.40, 0.45, 0.50, 0.55, and 0.60) through a combination of Raman spectroscopy, synchrotron X-ray diffraction, and dielectric spectroscopy. The aim is to gain insight into the complex phase boundary region responsible for the excellent electromechanical properties. The results demonstrate the correlation between local site substitutions based on the stoichiometric variations to the microstructure and dielectric properties. The dielectric response has been correlated with the BCT/BZT content displaying a maximum depending on the phase content. Additionally, in situ temperature-dependent Raman, permittivity, and pair distribution function (PDF) studies were performed from −60 °C to 130 °C to highlight the structure and phase evolution. In particular, the in situ temperature-dependent Raman measurements reveal sudden discontinuities in the vibrational modes that correspond to the structural changes in the perovskite structure. Therefore, the results of the permittivity response, based on the average of a large volume, are consistent with the local structural changes obtained by other techniques. Indeed, correlations of Raman, X-ray diffraction, and PDFs obtained from synchrotron X-ray total scattering data, along with permittivity measurements allowed the identification of the discrete ferro- to paraelectric phase transitions and a more robust characterization. The rotation and distortion of the octahedral caused by oxygen displacement are driving forces behind symmetry changes and phase transitions, explaining the mechanism of polymorphic phase transition based on A- and B-site substitution. Therefore, this work provides a comprehensive understanding of temperature and composition-dependent phase transitions in BCZ